MENGENAL HURUF HIJAIYAH MELALUI PERMAINAN KARTU HURUF BERWARNA - Kholis, Nur; Linda Astuti (AZZAHRA, 2020)
This study aims to improve the ability to recognize hijaiyah letters through the Color letter card game method. This type of research is a classroom action research, which is conducted in 2 cycles. The subjects in this study were children of Group B T RA Maarif Daarul Rahman Marga Tiga Lampung Timur, aged 5-6 years with a total of 25 children. The object of this research is the ability to recognize letters. Data collection techniques in this study are observation and documentation. The research instrument used was an observation guide. The data analysis technique used quantitative descriptive. The results showed that the ability to recognize Hijaiyah letters could be improved through a colorful letter card game. This is evidenced by the ability to recognize letters in the Pre-Cycle, the average percentage only reached 48%, then in Cycle I the average percentage increased to 76%, and the average percentage in Cycle II was able to increase up to 86%. The increase from Pre Cycle to Cycle I was 28%, and an increase from Cycle I to Cycle II was 10%. The positive contribution of this research is to provide information to the wider community that colored lettering cards can be used to improve children's literacy skills.